2019
DOI: 10.1038/s41598-019-49709-6
|View full text |Cite
|
Sign up to set email alerts
|

Process development for scale-up production of a therapeutic L-asparaginase by Streptomyces brollosae NEAE-115 from shake flasks to bioreactor

Abstract: L-asparaginase is a promising enzyme that has a wide range of significant applications including cancer therapy and starchy food industries. The statistical design of Plackett–Burman and face centered central composite design were employed to optimize L-asparaginase production by Streptomyces brollosae NEAE-115. As a result, a medium of the following formula is the optimum for producing L-asparaginase in the culture filtrate of Streptomyces brollosae NEAE-115: Dextrose 2 g, starch 20 g, L-asparagine 10 g, KNO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…Thus, Taxol was considered as one of the most important additions to the chemotherapeutic field in the late 20th century. The chronology of Taxol discovery, development and its clinical trials has been documented [ 23 , 30 , 32 , 33 , 34 ]. In the late 1980s, diterpenoid Taxane or Taxoid derivatives, Taxol and Docetaxel were introduced and proved to be effective in treatment of a variety of solid tumors including ovarian, lung, breast and bladder cancers [ 35 ].…”
Section: Chronology Of Taxol Its Derivatives As Antiproliferativementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Taxol was considered as one of the most important additions to the chemotherapeutic field in the late 20th century. The chronology of Taxol discovery, development and its clinical trials has been documented [ 23 , 30 , 32 , 33 , 34 ]. In the late 1980s, diterpenoid Taxane or Taxoid derivatives, Taxol and Docetaxel were introduced and proved to be effective in treatment of a variety of solid tumors including ovarian, lung, breast and bladder cancers [ 35 ].…”
Section: Chronology Of Taxol Its Derivatives As Antiproliferativementioning
confidence: 99%
“…Downregulation of the expression of Taxol genes upon subculturing of the endophytic fungi was reported frequently [ 29 ]. Thus, searching for novel fungal saprophytes having a stable molecular machinery system for conceivable production of Taxol independently is the ultimate objective for biotechnologists [ 22 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon sources are essential components in constructing cellular materials and are also used as energy sources [ 32 ]. Several earlier studies revealed the importance of additional nitrogen, carbon, and ion sources in the augmented production of this enzyme [ 33 ]. The organism Enterobacter aerogenes showed maximum l -asparaginase production in the presence of diammonium hydrogen phosphate and sodium citrate as nitrogen and carbon sources, respectively [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selected physicochemical properties namely peptone, casein, ammonium nitrate, beef extract, phenylalanine, yeast extract, urea, tyrosine, asparagine, glycine, valine, cysteine, methionine, glutamic acid, sucrose, starch, glucose, pH, and incubation time (day) were optimized using two factorial Plackett-Burman design to identify the significant variable tyrosinase production [24,25,39]. The nineteen variables were optimized by Plackett-Burman design.…”
Section: Bioprocess Optimization Of the Potent Fungal Isolate By Two-mentioning
confidence: 99%